Adhesion to medicines of elderly people with arterial hypertension and related factors (Research, Society and Development, 2021)
Objective: Assess medication adherence of elderly people with hypertension and its related factors. Methodology: This is a cross-sectional quantitative study with an exploratory-descriptive approach. This research is part of the macro-project "Relationship between Functional Health Literacy, medication adherence and functionality in elderly people in the family health strategy", which was carried out in 10 units, totaling 17 teams of the Family Health Strategy, which form the zone west of the city of Rio Grande-RS. Results: 264 elderly people with arterial hypertension participated in the study, 36.7% adherent and 63.3% non-adherent. The variables that had a statistically significant relationship with the mean medication adherence were having diabetes, taking medication for the digestive system/metabolism, and purchasing medication through the Unified Health System or through donation. Conclusion: Knowledge of the variables related to medication adherence in elderly patients with arterial hypertension contributes to directing interventions and actions carried out in coordination between health professionals, researchers, managers and policy makers, in order to improve access and adherence to treatments, thus minimizing harm resulting from this chronic disease.